France China Archives
France China Archives est une plateforme en libre accès qui inventorie les archives photographiques de la Chine conservées en France. Elle prend en compte les fonds privés et publics dont le contenu couvre la période allant des années 1840 à nos jours. Cette plateforme a été pensée pour fournir un espace numérique savant à l’étude de la variété des pratiques photographiques en Chine, tout en rendant les ressources en français accessibles à la communauté scientifique, aux étudiants et au grand public.
Keywords: _open access

Chinese Women's Studies Database glossary | Cheng Yu Tung East Asian Library
The Chinese Women’s Studies database is a unique resource for information about women’s social conditions, women’s movements and the rise of feminism in China. It is built upon a collection of card records donated to Cheng Yu Tung East Asian Library in the early 1980s by Dr. Bobby Siu, who was then a PhD student of Carleton University, Ottawa, Ontario. He collected the information and put it down on thousands of cards while he was conducting research on Chinese women. The records were all handwritten in either English or Chinese. Topics covered range from education and marriage to women's movement as well as revolutions and wars.
Keywords: _open access

Chinese collections at the Bodleian Libraries - Bodleian Libraries (2024)
Chinese books have been part of the Bodleian Libraries’ collections since the Library’s foundation in 1602. The first known acquisition of a Chinese book dates to 1604. Our founder – Sir Thomas Bodley – was instrumental in starting this collection, even though he did not speak or understand Chinese.  His handwriting appears in the 1604 book. The collection grew over the following four centuries and it continues to grow today. It is now one of the most significant Chinese rare book and manuscript collections outside China, containing the largest number of Chinese books that arrived in Europe in 17th century. As part of a ten-year project funded by Chung Hon Dak Foundation, we have digitised over 1,800 items, as well as worked with the local Chinese community to explore our collections in more detail.
Keywords: _open access

Collections numériques de l’Institut Français de Pondichéry - Inist (2024)
Keywords: _open access